Hierarchical TS-1 synthesized effectively by post-modification with TPAOH and ammonium hydroxide. Issue 51 (9th May 2016) - Wang, Baorong; Lin, Min; Peng, Xinxin; Zhu, Bin; Shu, Xingtian
Abstract : Hierarchical TS-1 with intracrystalline voids could be synthesized by post-modification with tetrapropyl ammonium hydroxide (TPAOH), however the process was supposed to be restrained by the charge balance effect. Abstract : Hierarchical TS-1 with intracrystalline voids could be synthesized by post-modification with tetrapropyl ammonium hydroxide (TPAOH), however the process was supposed to be restrained by the charge balance effect. In order to release the constraint, NH3 ·H2 O was introduced in the post-modification. The influences of the TPAOH/NH3 ·H2 O modification, the TPAOH concentration and the modification time on the physiochemical properties were studied. The dissolution process and recrystallization process were observed in the combined modification, and both of them were intensified by the NH3 ·H2 O introduced, indicating that the constraint on the OH − diffusion was released. Owing to the intensified processes, the TPAOH concentration and post-modification time could be reduced, and hierarchical TS-1 with relative high crystallinity, less defect sites and a larger secondary pore volume (about 0.18 cm 3 g −1 ) was achieved in 4 h. However, the combined-modification exerted little influence on the chemical composition and acidity, and the microporous properties were almost the same with that of TS-1 modified with TPAOH only. The secondary porosity in the combined-modified samples were mainly intracrystalline voids, and grooves on the surface were also found. Although extra-framework titanium species were created by the post-modification, part of the titanium was still in the framework position. The catalytic activity was evaluated by phenol hydroxylation and 1-octene epoxidation, and better catalytic activity was achieved for the improved accessibility of the active sites.